Burden of neurologic diseases in BRICS countries (1990 to 2021): an analysis of 2021 Global Burden of Disease Study - Shubham Chauhan; Shilpa Gaidhane; G. Padma Priya; Pawan Sharma; Mahakshit Bhat; Shilpa Sharma; M. Ravi Kumar; Aashna Sinha; Quazi Syed Zahiruddin; Navneet Dev; Ganesh Bushi; Diptismita Jena; et al. (Frontiers in Neurology, 2024)
BackgroundNeurological disorders are a major global health concern, especially in BRICS nations (Brazil, Russia, India, China, South Africa), where demographic and socio-economic changes have amplified their impact. This study evaluates trends in incidence, prevalence, mortality, and Disability-Adjusted Life Years (DALYs) associated with neurological diseases in these countries from 1990 to 2021, focusing on sex disparities and key risk factors.MethodsData were obtained from the Global Burden of Disease (GBD) 2021 database. Join point regression and Estimated Annual Percentage Change (EAPC) analyses were used to assess trends in neurological disease burden. Age-standardized rates for incidence, prevalence, and mortality were calculated, along with DALYs, and key risk factors were analyzed.ResultsChina showed the largest increase in incidence (7541.89 to 8031.37 per 100,000) and prevalence (26494.85 to 28534.79 per 100,000). Mortality increased in India (21.01 to 24.27 per 100,000) and South Africa (27.66 to 30.65 per 100,000), while China showed a decline (39.59 to 37.30 per 100,000). Brazil experienced a substantial rise in DALYs (1610.65 to 42024.59). Sex disparities showed higher DALY rates for females across all nations.ConclusionThe research highlights the rising burden of neurological disorders in BRICS nations, especially in China and Brazil due to aging populations and metabolic risks. It emphasizes the need for targeted interventions in India and South Africa, where increasing mortality rates and DALYs are concerning. Effective health policies should focus on early detection, managing metabolic risks, and implementing sex-specific strategies to address these issues.